2021
DOI: 10.3389/fpsyg.2021.795218
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Dynamic Work Environment on Employees’ Innovative Performance in the Post-epidemic Era – The Role of Job Crafting and Voice Behavior

Abstract: In today’s interconnected world, environmental uncertainty is higher than ever. Under the new economic normal, innovation-driven has become the key to the transformation and upgrading of various enterprises. Employees’ behavior affects the company’s innovative performance, but it is also deeply affected by the dynamic work environment. The sudden epidemic has greatly increased the environmental dynamics and uncertainties faced by individuals, and also caused many changes in individual behavior. However, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Thus, a turbulent environment will weaken the impact of effectual logic on employees’ innovative behavior. 63 , 64 Conversely, amid a relatively stable external environment and predictable future outcomes, employees are more inclined to deviate from prevailing thinking and actively engage in innovation. Therefore, low environmental dynamics will strengthen the impact of effectual logic on employees’ innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a turbulent environment will weaken the impact of effectual logic on employees’ innovative behavior. 63 , 64 Conversely, amid a relatively stable external environment and predictable future outcomes, employees are more inclined to deviate from prevailing thinking and actively engage in innovation. Therefore, low environmental dynamics will strengthen the impact of effectual logic on employees’ innovative behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural intelligence and dynamic work environment receive the highest ranking under the "External" component when compared to collectivism culture, corporate reputation, and search breadth. According to [37], employees perform more innovatively when they operate in a dynamic workplace. Employees with a higher cultural intelligence level are more motivated to connect often and productively with coworkers from other cultural backgrounds, which may boost their social context centrality and enable them to learn from others [50].…”
Section: Discussionmentioning
confidence: 99%
“…Rapid environmental changes put employees under more stress at work; thus, it is important to have a depth of knowledge to lessen the effects of uncertainty [36]. According to [37], employees perform more innovatively when they operate in a dynamic workplace. In a fast-paced workplace, having exceptional workers is essential to fostering organizational success.…”
mentioning
confidence: 99%
“…Turning to the influence of the work environment on innovative work behavior, Wang (2021) found that the dynamics of the work environment have an impact on innovative work behavior and performance.…”
Section: Work Behavior and Innovative Work Behaviormentioning
confidence: 99%
“…Educational leaders must reevaluate their management and leadership strategies to foster an innovative environment. Wang (2021) conducted a study on the impact of the work environment on employees' innovative work performance and found that the dynamics of the work environment significantly influence individual innovative work performance. Similarly, Shah et al (2022) investigated the influence of the workplace on employees' innovative work behavior and confirmed that the workplace is a strong predictor of innovative work behavior.…”
mentioning
confidence: 99%